BLOCKCHAIN BASED SCHEME CASHLESS SOCIETY - feri hari utami (Jurnal Media Infotama, 2023)
Abstract: Cashless Society in the world of the digital era is now growing rapidly where the buying and selling system uses the Cashless society system where the phenomenon of society utilizes digital payments when making financial transactions, so that the use of cash is minimal. This phenomenon was born as a result of a cashless economy where technological developments and digitalization is able to shift the use of physical money. This research builds on Design Science Research Methods as proposed in the work of Hevner et al and Peffer et al. It follows the design science research objectives of creating IT artefacts through problem identification and motivation, solution goal definition, design and development, demonstration, evaluation, and communication. Therefore, this study aims to establish a method of spanning IT artifacts (i.e., attribute-based access control) and instantiation (i.e., allowable blockchains using hyperledger fabrics). While the implementation process uses Cashless Society in the world of the digital era now, the current study has contributed by expanding efforts to integrate blockchain and business process management.